SP2.1.2Online near-peer practical skills teaching for medical students: A cross-sectional study. (28th October 2021) - Thirupathirajan, Vikram Ajit Rajan; Georgi, Maria; Hajra, Ankita; Myint, Fiona
Abstract: Aims: Medical students have reduced small-group teaching due to the COVID-19 pandemic. Online teaching typically involves large-groups and covers theoretical topics rather than practical skills. We investigated the effectiveness of a six-part online small-group tutorial series, teaching key practical skills to medical students in their first clinical year. Methods: Tutors taught using Microsoft Teams, with a tutor:student ratio being between 1:3 to 1:5. Tutorial themes were: examinations (Cardiovascular & Respiratory, Abdominal), A-E assessment and imaging (Thorax imaging & Histology, AXR & CT). Tutees completed a post-tutorial feedback form; the primary outcome was confidence improvement on the subject content. Likert Scales were used to measure the primary aim, with 1 corresponding to the worst outcome, and 4 corresponding to the best outcome. Results: 152 tutee feedback responses were analysed, a 60.0% response rate. Response numbers were lowest in the examinations tutorials. Mean tutee confidence improved markedly, from 1.954(SD 0.7918) to 3.414(SD 0.5572, p < 0.0001). This was highest in imaging tutorials (p < 0.05). Mean scores for effectiveness of delivery and effect of technical issues were 3.868(SD 0.3762) and 3.908(SD 0.3327) respectively. From tutors' feedback, 100% preferred teaching small-group over large-group sessions. However, only 33.3% prefer to teach online over face-to-face. Mean student engagement was rated at 3.417(SD 0.5149). Conclusions: Small-group teaching improves students' confidence in practical skills. Conducting this online is more effective for skills with little physical examination components and is something that can be expanded to a bigger cohort to maximise use of the online platforms.